Linguistics in Language Education. (July 2014) - Kumar, Rajesh; Yunus, Reva
This article looks at the contribution of insights from theoretical linguistics to an understanding of language acquisition and the nature of language in terms of their potential benefit to language education. We examine the ideas of innateness and universal language faculty, as well as multilingualism and the language–society relationship. Modern linguistics has studied language both as a phenomenon internal to individuals and as a social reality. We argue that understandings from both these areas together should be brought to bear on the conceptualisation of language teaching–learning. Multilingualism is indicative of tremendous language ability on the part of the speaker, and needs to be acknowledged as such, irrespective of which languages form part of the individual's repertoire. It is also of great significance to learners who need to participate in a pluralistic, democratic society. Indeed, the concept of 'a language' needs to be replaced by the idea of 'multilingualism'. We discuss a possible transformation in the goals and means of language education in the light of explanations and perspectives gained from the study of language. Since such a transformation would require a much greater and longer-term partnership between the study of language and language education, we suggest directions for future research. There does not seem to be an emphasis on linking these two fields in the literature at present; this article is an effort to establish the importance of addressing this gap.